(Retracted) Effects of Party System Fluidity on Legislative Oversight and Good Governance Indicators in Sub-Saharan African - Akbikesh Mukhtarova (Otoritas : Jurnal Ilmu Pemerintahan, 2020)
This article has been retracted due to double publication in another journal with the same article. Based on the clarification from the author, that it is true that he has submission and published the same article in another journal. These results were obtained when evaluating similarity checks on a regular basis on published articles. The similarity check results exceed 90 percent.One of the conditions of submission of a paper for publication in this journal is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.